Comprehensive review of Wolbachia research (1936–2024): Global landscape, mapping progress and themes - Manal Mohamed Elhassan Taha; Siddig Ibrahim Abdelwahab; Hafeez Yagoub Mohamed; Ahmed Jerah; Aied M. Alabsi; Saleh Mohammad Abdullah; Bassem Oraibi; Hassan Ahmad Alfaifi; Yasir Osman Hassan Babiker; Ibrahim Abdel Aziz Ibrahim; Saeed Alshahrani; Abdullah Mohammed Farasani; et al. (Parasite Epidemiology and Control, 2025)
Wolbachia, an obligatory gram-negative intracellular bacterium associated with Rickettsia, was initially identified in Culex pipiens mosquitoes and later in diverse invertebrates. This study utilizes bibliometric methodologies to quantitatively analyze Wolbachia research (WR), filling a gap in systematic analysis. Following PRISMA guidelines, original English papers were extracted from Scopus and analyzed using VOSViewer and Bibliometrix to assess performance indices, citations, co-word mapping, emerging themes, and the evolution of WR. Since its inception between 1936 and 1961, WR has grown to 4800 documents by 2024, with notable surges in 2022 and 2024. Scholars like O'Neill, Hoffmann, and Bourtzis have significantly influenced this field. Bradford's law highlights WR distribution among 876 sources, with 37.54 % of studies being collaborative. Six thematic areas have evolved toward practical applications, particularly in vector control and disease management. Emerging topics since 2015, such as “cytoplasmic incompatibility” and “arboviruses,” reflect growing interest in microbiology and disease control.